2009
DOI: 10.1590/s1413-70542009000600009
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da aplicação de silicato de cálcio em Brachiaria rizantha cv. Marandu sobre a população de ninfas do percevejo castanho das raízes Scaptocoris carvalhoi Becker, 1967, características químicas do solo, planta e produção de matéria seca

Abstract: Neste trabalho, objetivou-se avaliar o efeito de diferentes doses de silicato de cálcio sobre a população de ninfas de percevejo castanho das raízes em Brachiaria brizantha, nas características químicas do solo, planta e produção de matéria seca. O experimento foi conduzido em blocos casualizados, com cinco tratamentos e quatro repetições, totalizando 20 parcelas. Os tratamentos testados foram cinco doses (0, 0,5, 1, 2, e 4 t ha-1) de silicato de cálcio aplicadas junto com a adubação NPK na implantação da B. b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
1
0
1
Order By: Relevance
“…These results are consistent with those of [14], who found that the application of calcium silicate in increasing Table 1. The fresh and dry masses (g) of the aerial portions and roots of plants from two cultivars of sugarcane, one moderately resistant (MR) and another susceptible (S), with and without silicon (Si) application.…”
Section: Resultssupporting
confidence: 93%
“…These results are consistent with those of [14], who found that the application of calcium silicate in increasing Table 1. The fresh and dry masses (g) of the aerial portions and roots of plants from two cultivars of sugarcane, one moderately resistant (MR) and another susceptible (S), with and without silicon (Si) application.…”
Section: Resultssupporting
confidence: 93%
“…The supply of the mineral can be done through soil or foliar application. In most studies on silicon, calcium silicate was used directly applied to the soil, achieving a significant reduction of insects and damage on the plant (Souza et al, 2009). Although silicon is not an essential element for plant growth, its application helps the desorption of soil phosphorus increasing the availability of the mineral for plants and thus promoting plant growth as shown for Eucalyptus grandis (Carvalho et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Nós últimos anos, houve crescimento das pesquisas em que silicatos são utilizados para substituir o tradicional calcário, visto que, além de corrigir a acidez do solo e elevar o pH, com reações semelhantes ao calcário, o ânion silicato (H 3 SiO 4 -) disponibilizado, concorre com o ânion fosfato pelo mesmo sítio de adsorção, saturando, dessa forma, o ponto onde possivelmente seria adsorvido o P e, consequentemente, aumentando a disponibilidade desse nutriente para as culturas (Souza et al, 2009).…”
Section: Introductionunclassified